Specific Antibody and the T-Cell Response Elicited by BNT162b2 Boosting After Two ChAdOx1 nCoV-19 in Common Variable Immunodeficiency - Goda, Vera; Kriván, Gergely; Kulcsár, Andrea; Gönczi, Márton; Tasnády, Szabolcs; Matula, Zsolt; Nagy, Ginette; Bekő, Gabriella; Horváth, Máté; Uher, Ferenc; Szekanecz, Zoltán; Vályi-Nagy, István (Frontiers in Immunology, 2022)
Common variable immunodeficiency (CVID) patients have markedly decreased immune response to vaccinations. In this study we evaluated humoral and T cell-mediated responses against severe acute respiratory syndrome coronavirus-2 (SARS-Cov-2) with additional flow cytometric changes in CVID patients receiving booster vaccination with BNT162b2 after two ChAdOx1 nCoV-19. The BNT162b2 vaccine raised the anti-spike protein S immunoglobulin G over the cut-off value from 70% to 83% in CVID, anti-neutralizing antibody had been raised over a cut-off value from 70% to 80% but levels after boosting were significantly less in both tests than in healthy controls (*p=0.02; **p=0.009 respectively). Anti-SARS-CoV-2 immunoglobulin A became less positive in CVID after boosting, but the difference was not significant. The cumulative interferon-γ positive T cell response by ELISpot was over the cut-off value in 53% of the tested individuals and raised to 83% after boosting. This and flow cytometric control of cumulative CD4+ and CD8+ virus-specific T cell absolute counts in CVID were also statistically not different from healthy individuals after boosting. Additional flow cytometric measures for CD45+ lymphocytes, CD3+, and CD19+ cells have not shown significant differences from controls except for lower CD4+T cell counts at both time points (**p=0.003; **p=0.002), in parallel CD4+ virus-specific T-cell ratio was significantly lower in CVID patients at the first time point (*p: 0.03). After boosting, in more than 33% of both CVID patients and also in their healthy controls we detected a decrease in absolute CD45+, CD3+, CD3+CD4+, and CD3+CD8+, CD19+, and CD16+56+ cell counts. CD16+CD56+ cell counts were significantly lower compared to controls before and after boosting (*p=0.02, *p=0.02). CVID patients receiving immunosuppressive therapy throughout the previous year or autologous stem cell transplantation two years before vaccination had worse responses in anti-spike, anti-neutralizing antibody, CD3+CD4+T, CD19+ B, and natural killer cell counts than the whole CVID group. Vaccinations had few side effects. Based on these data, CVID patients receiving booster vaccination with BNT162b2 after two ChadOx1 can effectively elevate the levels of protection against COVID-19 infection, but the duration of the immune response together with COVID-19 morbidity data needs further investigation among these patients.